Vascular complications of type 2 diabetes mellitus beyond the reach of glycemic control - Tatiana Yul'evna Demidova (Endocrinology Research Centre, 2010)
Current therapeutic strategies of type 2 diabetes mellitus are aimed at reducing the risk of acute and late vascular complications by means of normalizationof glycemia, improvement of life quality and expectancy, minimization of socio-economic losses. The adequate glycemic control should besupplemented by screening for and correction of risk factors of cardiovascular disorders; it may help to prevent or delay the development of macrovascularcomplications.